MENINGKATKAN KEMAMPUAN SAINS ANAK MELALUI KEGIATAN EKSPLORASI BINATANG DI KELOMPOK A TK PGRI 7 TAPEN BONDOWOS - Ilzam Dhaifi; Iqmatul Qamariyah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2022)
One of the aims of learning science for early childhood is for children to acquire knowledge and have a scientific attitude. Through exploration activities, it will be easier for children to gain more knowledge and experience because of the unlimited nature of exploring. Based on the results of action research conducted in group A of TK PGRI 7 Tapen Bondowoso on Improving science through animal exploration activities, the following results were obtained: a) the implementation process consisted of two cycles. In cycle 1, the teacher invites children to observe animals from the pictures given and observe animals directly in cycle II. The teacher explains and asks questions about the animals that have been observed. Learning is carried out actively and fun. The teacher gives a lot of ice breaking and invites children to play so that children still enjoy the learning that is carried out. In the assessment carried out, the teacher refers to eight predetermined indicators. Learning runs effectively and efficiently as evidenced by the results of observations and learning outcomes obtained, namely in the first cycle reaching 52%, and increasing in the second cycle 78%. while the classical mastery target set is 75%.